PERFORMANCE OF E-BANKING AND THE MEDIATING EFFECT OF CUSTOMER SATISFACTION (International Journal of Food and Nutritional Sciences, 2022)
The role of banks in modern economies is ubiquitous. The health of a country's banking system is crucial to the expansion and development of its economy. In order to achieve a wide range of investment goals, the public's savings need to be mobilized and made available via a reliable banking system. In this context, financial institutions are seen as the backbones of the country's economic growth and prosperity. These monetary operations form the backbone of today's global economy. Every single corner of the country now has access to banking services. When it comes to a country's economic development, banks are a key facilitator. Similarly, banking has developed into an integral aspect of most people's life. There is no way to sustain a human life without banks and other forms of financial activity. India has both an organized and disorganized banking system. The aims of the current investigation are as follows:to outline the development of e-banking in India, to assess Level of Customer Satisfaction e- Banking and to understand customer perceptions of e-banking services. Convenience sampling was used to choose 200 participants to assess the relationship between E-Banking performance and customer satisfaction as a mediator. Using Google forms, we were able to gather information from a representative sample of the population. Banks may better meet the needs of their clients and save time and effort by embracing technological advancements. Banking in India has been revolutionized by the rise of digital technologies.